Online Feedback in Interactive Blogging: Cultivating Students’ Writing Performance and Learning Engagement - Teguh Sulistyo; Oktavia Widiastuti; Siti Mafulah; Yunita Puspitasari; Tim Holland (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2023)
Integrating Information and Communication Technologies (ICT) into language learning has shifted how English classes are administered. The shift in teaching instruction from pen and paper-based activities to online-based approaches has led to interactive blogging to make the classes more authentic, motivating, and communicative. Thus, this paper mainly examines two significant issues: 1) how interactive blogging benefited the writing class when online feedback took place and 2) how the EFL students actively participated in the interactive blogging atmospheres. This study employed school-based action research involving 30 students majoring in the English Language Program of a university in Malang, Indonesia, who actively participated in the study. The data were taken from interviews, open-ended questionnaires, and writing tests. The findings revealed that online feedback in interactive blogging increases students’ writing performance covering CAF (complexity, accuracy, and fluency), and it enables students to interact more frequently with their teacher and classmates inside and outside the classroom. This indicates that teachers must empower students with technologies and more student-student and student-teacher interactions in writing classes. However, it is not as easy as paper and pen-based writing activities when giving and understanding online feedback.